Eisenmenger Syndrome in Pregnancy: When Is It Time for ECMO?. Issue 10 (15th November 2018) - Meng, Marie-Louise; Fu, Annie; Westhoff, Carolyn; Bacchetta, Matthew; Rosenzweig, Erika B.; Landau, Ruth; Smiley, Richard
Abstract : We report the case of a 21-year-old primiparous woman at 22 weeks gestation who presented with a large uncorrected ventricular septal defect, severe pulmonary hypertension, and Eisenmenger syndrome. The patient elected for termination of pregnancy, which was performed under regional anesthesia. Hemodynamic changes apparently associated with uterine contraction immediately after termination resulted in increased right to left shunting across the ventricular septal defect requiring urgent venovenous extracorporeal membrane oxygenation. Thrombocytopenia and systemic anticoagulation for extracorporeal membrane oxygenation presented a challenge for removal of the epidural catheter. Pulmonary hypertension was managed and she was discharged on postoperative day 35.